The potential of spiritual leadership in workplace spirituality - Naidoo, Marilyn ca. 20./21. Jh. (Koers, 2014)
We live in the transition period between the old definition of work as survival and the new definition of work as livelihood. A new awareness of the value of spirituality can add to the innovation and creative capacity of ‘human capital’, increased authenticity in communication and has the potential for increased ethical and moral behaviour. For organisations wanting greater commitment this means opening up the conversation to include dimensions of soul and spirit that have been traditionally left at the office door. Workplace spirituality has potential for leadership development as it allows employees and leaders to act from personal truth, integrity, values and ethical practice. Spiritual leadership taps into the fundamental needs of both leader and follower for spiritual survival so that they become more organisationally committed and productive. This article focuses on the potential of spiritual leadership to transform and to contribute to the success of an organisation.